Kontekstualisasi Doktrin Ibadah dalam Irisan Pandemi Coronavirus Disease of 2019 (Covid-19) - Edyar, Busman (AL-ISTINBATH : Jurnal Hukum Islam, 2021)
This paper aims to elaborate on the contextual rituals of Muslims in Indonesia as decreed by Indonesian scholars such as the Indonesian Ulema Council (MUI), Muhammadiyah, and Nahdhatul Ulama (NU) in connection with the Covid-19 pandemic. The type of research used is a literature study with a qualitative approach which is analyzed by means of content analysis. The result of the research is that there is a significant breakthrough in the ritual of worship which has been standard in the doctrine of al-ashlu fi al-ibadah al-tauqif wa al-ittiba'. The breaking of this worship protocol at least occurs in the principle of congregational prayer and its procedures, the use of masks during prayer, the implementation of Friday prayers, Eid prayers, and the organization of the corpse. Meanwhile, Indonesian clerics such as MUI, Muhammadiyah (through the Tarjih Council) and NU (through Bahsul Masail) justified this breach. The maslahah factor in order to avoid the risk of transmitting the Covid-19 virus, is the main reason for the justification of these scholars. This study strengthens the existence of Islamic legal theories which are summarized in the fiqh rules in answering social problems that have a wedge with religious rituals. So it is illustrated that Islamic doctrine is rigid in its provisions but remains flexible in application.